Evaluasi Investasi Properti Rumah Tipe 30/60 Pada Perumahan Insani Regency Lamongan - Imam Sururi; Hammam Rofiqi Agustapraja (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
AbstractInvestment is an attempt to invest capital in a certain time to obtain profits in the future.Housing is a group of houses that functions as a residential environment or human dwellingthat is equipped with environmental infrastructure that is basic equipment such as the physicalenvironment, such as the provision of drinking water, landfills, availability of electricityresources, etc., which allows the residential environment to function as it should be. While thehouse is a place to let go of fatigue, a place to live for the family, a place for family protection,and also a place as a social status. The purpose of this study was to determine the feasibility ofInsani Regency Lamongan housing investment. The method used to analyze the investmentfeasibility is the Net Present Value Method. From the results of this research, the LamonganRegency Insani Housing showed that it was feasible because it produced a NPV of Rp234,992,925.